Ketika Martabat dan Kebebasan Perempuan dirampas: Merefleksikan Puisi Kidung Agung 8:8-10 Melalui Perspektif Feminis - Kawatu, Lily Ivone; Fernando, Andreas; Pasaribu, Andri; Zebua, Arianto (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2024)
This article aims to reflect on the dignity and freedom of women's rights found in the poem Kidung Agung 8:8-10. The dignity and freedom of women's rights are still something that is ambiguous in society, especially in Indonesia and countries that adhere to the patriarchal system. This article responds to the issue of gender-based freedom of women's rights by conducting theological reflection on Song of Songs 8:8-10 through a feminist perspective. Therefore, this article voices the author's experience and perspective on the issue of dignity and freedom of rights that are still limited and provides strengthening discourse on the elimination of deprivation of rights to women in any form. Through this study, it is revealed that gender inequality in the structure of a patriarchal society contributes to the inequality of freedom rights, in this case women as the object of harm. Therefore, advocacy is needed for women as victims of freedom rights from a system that positions women as powerless.AbstrakArtikel ini bertujuan untuk merefleksikan martabat dan kebebasan hak perempuan yang terdapat dalam puisi Kidung Agung 8:8-10. Martabat serta kebebasan hak perempuan masih menjadi sesuatu yang rancu di kalangan masyarakat khususnya indonesia dan negara penganut sistem patriarkis. Artikel ini merespon isu kebebasan hak perempuan berbasis gender dengan melakukan refleksi teologis atas Kidung Agung 8:8-10 melalui perspektif feminis. Oleh sebab itu, Artikel ini menyuarakan pengalaman dan perspektif penulis terhadap isu martabat dan kebebasan hak yang masih terbatas dan memberikan penguatan diskursus penghapusan perampasan hak pada perempuan dalam bentuk apapun. Melalui kajian ini terungkap bahwa ketidaksamaan gender dalam struktur masyarakat patriarki menyubang terjadinya ketimpangan hak kebebasan dalam hal ini perempuan sebagai objek yang dirugikan. Oleh karena itu, diperlukan advokasi terhadap perempuan sebagai korban kebebasan hak dari sebuah sistem yang memposisikan perempuan sebagai yang tidak berdaya.